A painted ridge : rock art and performance in the Maclear District, Eastern Cape Province, South Africa - Witelson, David Mendel, (Cambridge monographs in African archaeology ;, 2019)
The San (Bushmen) practice of rock painting is examined in this text. David Witelson explores a suite of spatially close San rock painting sites in the Maclear District of South Africa's Eastern Cape Province. As a suite, the sites are remarkable because, despite their proximity to each other, they share patterns of similarity and simultaneous difference. They are a microcosm that reflects, in a broad sense, a trend found at other painted sites in South Africa. The bygone and almost unrecorded practice of San rock art is considered relative to ethnographically well-documented and observed forms of San expressive culture. The approach in the book draws on concepts and terminology from the discipline of performance studies to characterise the San practice of image-making as well as to coordinate otherwise disparate ideas about that practice.